Funiculars in Lithuania: from the fruit basket to Gediminas Hill - Maskeliūnaitė, Lijana (Transport, 2024)
Technological advances in transport of the 20th century include aeroplanes, human spaceflight and Moon landings, submarines, and magnetic levitation trains. In the fast-paced world of technology, the achievements of previous centuries are often forgotten. One of the examples of human ingenuity is the funicular railway. Its technology has hardly changed over the years. Using a simple pulley system, passengers and freight are still lifted steep slopes with minimal energy consumption. This demonstrates the lasting value of simple solutions and engineering intelligence. The article discusses the world’s funiculars and their design characteristics. A correlation analysis for the number of funiculars per country (N) and the country mountainousness index (M) has been carried out. 3 types of regression models have been developed and their determination and correlation coefficients have been calculated. The highest correlation coefficient values are for quadratic and linear mathematical models. The critical values of the correlation coefficients were calculated and compared with the correlation coefficients obtained from the study. For all 36 countries, the correlation coefficient for N and M variables is above the critical value only when a quadratic regression model is used. The correlation coefficients for all models are above the critical value for the 15 economically advanced and tourism-developing countries. The study shows that the number of cable cars in economically developed countries is more strongly correlated with the degree of mountainousness of the country in question.